Power Enhancement of Partial Shaded PV Array by Optimizing the Electrical Connection of Module - Wang Mengyao (MATEC Web of Conferences, 2015)
The maximum output power (Pmax) generated from photovoltaic (PV) array will be apparently reduced if the array is partially shaded. In order to enhance Pmax generated from partial shaded PV array, several interconnection schemes of array are proposed. Among these schemes, the totally cross tied (TCT) scheme and the recently proposed static scheme are widely discussed. It was reported that Pmax produced with static scheme is equal to the TCT scheme even under worst conditions. However, in these simulations the illumination of every single module is assumed to be uniform, but in urban environments the illumination of modules on the edge of shadow is more likely to be non-uniform. In this paper, first, a comprehensive circuit-level simulation, which is implemented in PSpice, has been done to investigate performance of PV array with both TCT scheme and static scheme under different partial shading conditions. And the results show that Pmax generated from static scheme is higher than that form TCT scheme if the illumination of every single module is uniform, however if some modules are partially shaded, the Pmax with static scheme is more likely less than that with TCT scheme. Then, the electrical connection of a module is improved for the purpose of enhancing Pmax under partial shading conditions in which some modules in the array are partially shaded. And the simulation results show that Pmax is apparently increased by employing the improved modules.